Determination of Energy Requirements for Dry Land Tillage Using Spatial Variability Technique - Ng, Eng Boon (2006)
This study describes the utilization of spatial variability technique in obtaining the tillage energy requirements of disk plowing operation, first rotary tilling after disk plowing operations and second rotary tilling after first rotary tilling and disk plowing operations. Spatial variability of soil terrain characteristics, tractor implement performances and tillage qualities were measured across two field plots using the mapping system that consists of a Massey Ferguson 3060 instrumented tractor with built-in data acquisition system, differential global positioning system (DGPS) and transducers, mounted-type soil penetrometer-shearometer unit and trailed-type soil surface profile digitizer, respectively. The collected soil terrain characteristic and tractor-implement performance data sets were transferred to ArcView GIs software to produce spatial interpolated surface maps for further statistical analyses. SAS statistical software was used to perform univariate, correlation and stepwise multiple regression analyses to generate mathematical models for tdlage energy requirements. Models for tractor travel speed, draft and fuel consumption with respect to the soil terrain characteristic and tractor-implement performance variables were successfully developed for disk plowing operations and models for tractor travel speed, PTO power and fuel consumption with respect to the soil terrain characteristic and tractor-implement performance variables were successllly developed for first rotary tilling after disk plowing operations and second rotary tilling after first rotary tilling and disk plowing operations. Mean values of soil moisture content, average elevation height, degree of tilth, random roughness index of the soil surface profile, sensing error, PTO power and fuel consumption data sets resulting from first rotary tilling after disk plowing operations and second rotary tilling after first rotary tilling and disk plowing operations at rated and reduced engine speed were also documented for comparison purposes. Evidence trends were shown on soil random roughness index, PTO power, and fuel consumption when subjected to different tillage operations and engine speeds.